Liberal Protestantism and Christian Studies at Kyoto University. Einleitung - Graf, Friedrich Wilhelm (Zeitschrift für neuere Theologiegeschichte, 2020)
By the end of April 1923, Paul Tillich’s Das System der Wissenschaften nach Gegenständen und Methoden (1981: The System of the Sciences according to Objects and Methods) was published by the German publishing house Vandenhoeck & Ruprecht in Göttingen. Based on numerous source documents from the publishers’ archives and particularly on the correspondence between the publishers Wilhelm and Gustav Ruprecht, hitherto unknown but now edited and commented on here, the present article explains that Tillich wrote his System of the Sciences primarily for the publisher. It was Emanuel Hirsch who established the connection between them as the publishing house was looking for a new editor for their popular series Wege zur Philosophie (Ways to Philosophy), published since 1911. After Hirsch having brought Tillich into play, Wilhelm Ruprecht could convince the Berlin “Privatdozenten” to become the new editor of the series. As to the series, Tillich unfolded the concept of a comprehensive system design which covered 65 topics, i. e. forthcoming volumes. When the publisher then demanded that Tillich prove his abilities to write comprehensively in common language by providing a sample of a first issue of the series, he began to work on his System der Wissenschaften. Although this text contained all sorts of ideas and concepts, it was certainly not very well suited as an introduction to a series of popular accounts of the central themes and matters of philosophy. In the end, the System was published, although not as a volume of the series as having been announced by the publishing house in 1922, but as a text in its own right.